Study of extensometric measurements in non tidal frequency domain at the Russian and Slovak stations - BRIMICH, Ladislav; LATYNINA, Lyudmila Alexandrovna; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2021)
The study of the Earth’s crust deformations caused by the Sumatra-Andaman earthquake (26th December, 2004) at large distances from its focal point is the main subject of the paper. The extensometric measurements at stations Protvino (Podmoskovie area) and Baksan (Caucasus) reveal the concordant pattern. A comparative analysis of the measured data for the Protvino and Vyhne (Western Carpathians) was performed for the same time period. The correlation of the observations within three months before the earthquake is quite low. The substantial correlation was observed for the time span of the earthquake and for the following two months. Consequently, the Sumatra-Andaman earthquake manifested itself at the distant points by increasing mobility of the Earth’s crust. The mechanisms of this coupling are outlined.